Chronomodulated drug delivery system: A comprehensive review on the recent advances in a new sub-discipline of ‘chronopharmaceutics’ - Bisht, Rohit (Asian Journal of Pharmaceutics (AJP), 2014)
With the advancement in the field of chronobiology, modern drug delivery approaches have been elevated to a new concept of chronopharmacology, that is, the ability to deliver the therapeutic agent to a patient in a staggered profile. The mammalian circadian pacemaker resides in the paired suprachiasmatic nuclei and influences a multitude of biological processes, including the sleep–wake rhythm. Clock genes are the genes that control the circadian rhythms in physiology and behavior. Twenty-four hours rhythms are demonstrated for the function of physiology and the pathophysiology of diseases. The effectiveness and toxicity of many drugs vary depending on the dosing time. Such chronopharmacological phenomena are influenced by not only the pharmacodynamics, but also the pharmacokinetics of medications.The underlying mechanisms are associated with the 24-hour rhythms of biochemical,physiological, and behavioral processes under thecontrol of the circadian clock. New technology for delivering medications precisely in a time-modulated fashion, by bedside or ambulatory pumps, is being developed to manage human diseases. From the point of view of pharmaceutics, the application of a biological rhythm to pharmacotherapy may be accomplished by the appropriate timing of conventionally formulated tablets and capsules, and a special drug delivery system, to synchronize the drug concentrations with the rhythms in the disease activity. Therefore, the present article gives an overview of the dosing time-dependent alterations in the therapeutic outcome and safety of the drug. The underlying mechanisms and usefulness are introduced from the point of view of chronopharmacology and chronotherapy.